Impact of Board Diversity on Corporate Social Responsibility of Listed Oil and Gas Firms in Nigeria - Olanrewaju, Issa Saheed; Ishola, Abdulkadir Kayode; Nurudeen, Sanni Olawale; Ayuba, Ibrahim Abubakar (International Journal of Management and Sustainability, 2020)
This study investigates the impact of board diversity on corporate social responsibility in a developing country context. Board diversity was measured using four dimensions (board independence, board gender diversity, board professionalism and board nationality. We test our hypotheses using data obtained from annual report of eight (8) listed oil and gas firms on Nigeria Stock Exchange (NSE) from 2012 to 2018. Diagnostic test such as, multicollinearity, heteroscedasticity and Hausman tests were conducted to validate the results. Applying Panel corrected standard error (PCSE) regression, the result reveal that board independence, board gender diversity and board diversity have significant positive impact on corporate social responsibility. In contrast, board professionalism has insignificant relationship with corporate social responsibility. In line with Stakeholder theory, our results suggest that board diversity can be seen as an effective mechanism to enhance CSR participation and spending as diversity of boards improves the ability of firms to meet the needs of their broader stakeholder groups. Our study contributes to a better comprehension of the potential value of the diversity of boards. It is therefore recommended that management of listed oil and gas firms need to maintain diverse balanced boards in terms of gender, independence, and expertise to enhance protection of stakeholder’s interest and the reduction of manager’s opportunistic tendencies behind CSR investment.